Single hole direct injector simulation validation and parametric sensitivity study - Mohamad Hafidzul Rahman, Alias; Mohd Fadzil, Abdul Rahim; R. A., Bakar (IOP Publishing, 2019)
This paper presents a parametric study conducted on electronically controlled solenoid direct fuel injector running on compressed natural gas. The purpose of the study is to identify the influential injector parameters on the output mass flowrate. These injector parameters are to be optimized in the next stage of the study. The parametric study is conducted using zero-dimensional, first principle injector model, which consist of electromagnetic, mechanical and flow sub-models. In the current study, seven (six input and one output) parameters have been analysed which are the injection pressure, injection duration, nozzle diameter, armature mass, the input voltage, spring constant and the output mass flow rate. Each input parameters are varied in the prescribed range based on the literature. Based on the study, the most influential parameters (in rank) are the nozzle diameter, the armature mass and the injection duration. The input voltage, the injection pressure and the spring constant were found to have no impact on the injector mass flow rate based on the values of the parameter’s sensitivities. Based on the results, the potential parameters to be optimized are identified.